(untitled) (Fiep Bulletin - online, 2013)
Football is one of the most practiced sports in the world. According to a survey conducted by the Federation Internationale de Football Association (FIFA), maximum body of worldwide soccer, around 240 million people practice the sport regularly throughout the world. As in many sports, football categorizes individuals by age, in order to match the competition. However, considering only the chronological age of individuals can cause inequality in training, and also decrease’s the number of opportunities for some. Therefore, the purpose of this study is to see if the birth date has influence in anthropometric variables, for young footballers, included in the infant category, under-15. The sample was composed of 34 male athletes, aged between 14 (n = 18) and 15 (n = 16) years, members of soccer teams from Curitiba. The G14 groups with Chronological Age (JI) average 14.55 ± 0.25 and G15 with IC average 15.49 ± 0.25 showed significant differences with p <0.01. In anthropometric variables, no differences were observed in stature (EST) = 172.27 cm G14 and G15 = ± 6.81 cm ± 5.08 and 175.87% of fat, G14 = 10.24 ± 0.95 and G15 = 10 , 70 ± 1.03. Significant differences were observed in variables body mass (CM), G14 = 59.69 ± 8.68 and G15 = 69.53 ± 5.88 and BMI, G14 = 20.07 ± 2.31 and 22.47 ± G15 = 1.67. We can conclude with this study that the advancement of age in the category is related to a substantial increase in body mass of footballers. This difference appears to be mainly by the increase in lean body mass, since no differences were found in the EST and% fat.